Battery technologies and functionality of battery management system for EVs: Current status, key challenges, and future prospectives - Waseem, Mohammad; Ahmad, Mumtaz; Parveen, Aasiya; Suhaib, Mohd (Journal of power sources, 2023)
Research and development towards electric vehicles (EVs) are getting exclusive attention because of their eco-friendly nature, suppression of petroleum products, greener transport, and zero carbon emission at the tail point. The battery is a crucial component of an EV. A review of progress and hurdles of (i) current states of EVs, batteries, and battery management system (BMS), (ii) various energy storing medium for EVs, (iii) Pre-lithium, lithium-based, and post-lithium batteries for EVs, (iv) numerous BMS functionalities for EVs, including status estimate, battery cell balancing, battery faults diagnosis, and battery cell thermal monitoring methodologies, (v) AC, DC, and wireless EV charging techniques, (vi) key challenges and barriers for EVs, and (vii) future work and prospectives of EVs, are outlined in this article. The goal is to uncover the prime features, merits & demerits, new technology development, future barriers, and prospects for advancing the electrification of the transport system. This perilous assessment predicts the progress of battery trends, method regarding batteries, and technology substituting batteries. Next, lithium-metal, lithium-ion, and post-lithium batteries technologies such as metal-air, alternate metal-ion, and solid-state batteries will be dynamically uncovered in the subsequent years. Wherein, implementing emerging computer-based technology and data-driven modelling can predict the electrochemical behaviour of the batteries. Further, integration of a move-and-charge (wireless power transfer) scheme can be deployed on lane roads to reduce dependency on batteries. To exchange data, energy, and sophisticated BMS with EVs in the future, smart technologies like IoT, blockchain, cloud computing, and digital twin will be used. [Display omitted] •Batteries before to lithium, lithium-based, and post lithium are presented.•Comparing and describing the various functions of battery management systems.•Advanced techniques for identifying battery faults are compared and described.•The description of an electric vehicle wireless power transfer charging system.